2021
DOI: 10.1111/odi.14091
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epstein–Barr virus, cytomegalovirus and lipocalin with periodontitis in type 2 diabetic subjects

Abstract: Over the years, the role of microorganisms has evolved as a major causative factor in the aetiology of the periodontal disease (Palenstien Helderman, 1981). Products of periodontal bacteria, which mainly comprise of lipopolysaccharides (LPS), enzymes and toxins, induce an inflammatory response to the host (Wang & Ohura, 2002). This uncontrolled, over-exuberant inflammatory response in chronic periodontitis associated with an oxidative stress-induced inflammatory pathogenesis, can be a risk for various systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Similar to other studies, we did not nd an association between plaque control scores and periodontal pocket depth in CMV positive patients (Table 4), regardless of the higher prevalence of this herpesvirus observed in periodontal patients [51]. Whereas several studies have reported a high prevalence of EBV [18][19][20]22] and CMV [52,53] associated to an increased risk of periodontitis. Although the potential herpesviral-bacterial coinfection has not been completely elucidated, their synergistic interaction is becoming increasingly supported by a body of evidence.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies, we did not nd an association between plaque control scores and periodontal pocket depth in CMV positive patients (Table 4), regardless of the higher prevalence of this herpesvirus observed in periodontal patients [51]. Whereas several studies have reported a high prevalence of EBV [18][19][20]22] and CMV [52,53] associated to an increased risk of periodontitis. Although the potential herpesviral-bacterial coinfection has not been completely elucidated, their synergistic interaction is becoming increasingly supported by a body of evidence.…”
Section: Discussionsupporting
confidence: 88%